Survey to Immune System and Internet of Things in Terms of Self-management - Shatha Habeeb (Journal of Madenat Alelem University College, 2020)
The rapid development in the world of Internet networks led to the emergence of Internet of things and Web of things which in turn requires speed and self-management for the success of the transmission of information and self-interaction between request and response to the latest event.  In this research we clarify the similarity main points between the workflow of the immune system in humans, Artificial Immune Systems which work to protect the body from the strange things that enter the body and which require self-management and the Internet of things as an interconnected network consisting of a combination of things which permits communications between objects, machines and anything else with each other. IoT can be defined as a system comprised of things in the real world, these things are attached to sensors which are connected to the Internet through wired or wireless connection structure that requires self-management.